1997
DOI: 10.1108/09564239710166245
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of service recovery options

Abstract: As the importance of service quality, as both marketing strategy and competitive advantage, gains more and more recognition, efforts to recover from poor service delivery are receiving increased attention. Yet, much of the literature is based on anecdotal accounts rather than theoretical conceptualizations or rigorous empirical assessment. At least one retailing study has shown that more than 70 per cent of customers who complain can be persuaded to continue shopping with the offending retailer provided that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
254
2
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(284 citation statements)
references
References 46 publications
8
254
2
12
Order By: Relevance
“…Accordingly, service quality has been receiving much prominence because of its obvious relationship to costs 2 , financial performance 3,4 , customer satisfaction [5][6][7] and customer retention [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, service quality has been receiving much prominence because of its obvious relationship to costs 2 , financial performance 3,4 , customer satisfaction [5][6][7] and customer retention [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Apology, attentiveness and being proactive are all interpersonal tactics applied to the service delivery process. However, Boshoff (1997) pointed that a mere apology without compensation might not be sufficient to satisfy unpleasant customers -complainers need to be at least returned to their original position before the failure happens [7]. In regard to the relevance between failure and monetary compensation, Schneider and Bowen (1999) particularly indicated that customers tend to desperately protect their financial well-being in the face of service failure.…”
Section: Strategies Of Service Failure Recoverymentioning
confidence: 99%
“…), and being respectful, polite and courteous during the service recovery process (Bitner, Booms, & Mary, 1990;Blodgett, Hill, & Tax, 1997;Mattila & Patterson, 2004;Sparks & McColl-Kennedy, 2001). While evidence for the "recovery paradox" is sparse and varied, it is generally agreed that effective service recovery can redirect dissatisfied customers to a state of satisfaction and it go a long way towards limiting the harmful impact of service failure (Boshoff, 1997;Boshoff & Leong, 1998;Michel, 2001). Consequently, past studies have applied the Justice Theory to evaluate service recovery efforts following service failure and included distributive justice, interactional justice, and procedural justice (Patterson, Cowley, & Prasongsukarn, 2006;Schoefer, 2010).…”
Section: Service Recoverymentioning
confidence: 99%
“…When an individual perceives that benefits have not been allocated equitably, he/she experiences distress, which in turn motivates him/her to restore distributive justice. Studies have provided empirical evidence that perceived fairness of tangible outcomes has a positive effect on recovery evaluation (Boshoff, 1997;Goodwin & Ross, 1992;Smith, Bolton, & Wagner, 1999).…”
Section: Customer Satisfactionmentioning
confidence: 99%